The Art of Staying Neutral : The Netherlands in the First World War, 1914-1918 - Abbenhuis, Maartje (Amsterdam University Press, 2006)
The Art of Staying Neutral offers a fascinating insight into the problems and challenges associated with neutrality in an age of 'total war'. It explains how the Netherlands upheld and protected its non-belligerency during the First World War despite constant interference from its warring neighbours. Staying neutral was an artform that the Dutch managed to master through clever diplomacy, conscientious adherence to international laws, comprehensive mobilisation of its armed forces, regular patrols of its territorial boundaries, careful policing of its citizens, and a decisive measure of good fortune. The Art of Staying Neutral makes important contributions to the study of neutrality and the domestic history of the Netherlands in this seminal world event.
The Art of Staying Neutral geeft boeiende inzichten in de problemen en uitdagingen van neutraliteit in een tijdperk van 'totale oorlog'. Het boek zet uiteen hoe Nederland zijn neutrale status tijdens de Eerste Wereldoorlog wist te handhaven en beschermen, ondanks de constante druk van buren die wél in oorlog waren. Neutraal blijven was een kunst die de Nederlanders beheersten door middel van uitgekiende diplomatie, zorgvuldige naleving van internationale wetten, uitgebreide mobilisatie van gewapende eenheden, regelmatige patrouillering langs de landsgrenzen en nauwgezette controle van de onderdanen, maar ook dankzij een flinke dosis geluk. The Art of Staying Neutral levert een belangrijke bijdrage aan de studie van neutraliteit en besteedt ook volop aandacht aan de nationale en internationale gevolgen van de opstelling van Nederland tijdens deze ingrijpende periode uit de wereldgeschiedenis.
English
Keywords: History; geschiedenis; history, geography, and auxiliary disciplines